Cutaneous Rosai-Dorfman Disease Showing Pruritic Macules - Ota, Mayumi; Nobeyama, Yoshimasa; Asahina, Akihiko (Archives of Clinical and Medical Case Reports, 2021)
Cutaneous Rosai-Dorfman disease (CRDD) is a rare skin-limited form of Rosai-Dorfman disease, a benign histiocytic proliferative disorder commonly affecting lymph nodes. Here, we report a case of CRDD characterized by pruritic reddish-brown macules, which we initially misdiagnosed as post-inflammatory pigmentation due to uremic dermatitis. A 64-year-old Japanese man was referred to us with an 8-month history of pruritic eruption located in the trunk and limbs. He had been receiving dialysis for chronic renal failure for 24 years. Physical examination revealed multiple reddish-brown macules measuring 1–10 cm in diameter with scratch marks irregularly distributed on the trunk and limbs. Pruritic score on the Numeric Rating Scale (NRS) was 9 out of 10. The patient displayed no extracutaneous involvements such as lymphadenopathy, fever or weight loss. Histopathological examination of the reddish-brown macules showed dense infiltration of histiocytes with lymphocytes and plasma cells in the dermis covered by epidermis with a faintly pigmented basal layer. Some histiocytes had taken in red blood cells, representing so-called emperipolesis. Immunohistochemical analyses of histiocytes showed reactivity to anti-S-100 protein antibodies and anti-CD68 antibodies, but not to anti-CD1a antibodies. Based on these findings, CRDD was diagnosed. This case suggests that CRDD may present with: i) macular lesions in the active phase; and ii) severe pruritus.